If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(7h + -15) = 9 + 18h Reorder the terms: 3(-15 + 7h) = 9 + 18h (-15 * 3 + 7h * 3) = 9 + 18h (-45 + 21h) = 9 + 18h Solving -45 + 21h = 9 + 18h Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-18h' to each side of the equation. -45 + 21h + -18h = 9 + 18h + -18h Combine like terms: 21h + -18h = 3h -45 + 3h = 9 + 18h + -18h Combine like terms: 18h + -18h = 0 -45 + 3h = 9 + 0 -45 + 3h = 9 Add '45' to each side of the equation. -45 + 45 + 3h = 9 + 45 Combine like terms: -45 + 45 = 0 0 + 3h = 9 + 45 3h = 9 + 45 Combine like terms: 9 + 45 = 54 3h = 54 Divide each side by '3'. h = 18 Simplifying h = 18
| -7(7-3x)=-175 | | 16x+8=-3 | | q/8-5=9 | | -17w+7(17w+12)=18w | | 5x+2-6x=-11 | | 702/u=27 | | 18.94+15.8g=-3(-18.8g+11.28) | | a-42=-4a-7 | | 5(8+2x)=-30 | | -2x+4-2x=-12 | | 18.94-15.8g=-3(-18.8g+11.28) | | 5+5d=80 | | 7r+3-3r=15 | | X-5+9x=40 | | z^2+(12+6i)z+(11+24i)=0 | | 80=18+2p | | 2x+9+4x=-57 | | 4.3f-14.65-19.08=-3.13+12.8f | | -x+2x+5+2x=-25 | | 6n^2-18n-18=-6 | | 9v-17=73 | | 2[5x+8]=6x+20 | | 9.7u-18.15-2.5u=11.8u+7.15 | | 43=8m+3 | | -2x+8-6x=-32 | | 15.5k-19.69+7.75=0.03+16.4k | | 7x-8-3x=20 | | 3x+10+4x=38 | | 25x+8=6x+20 | | -7+6x-5x=-19 | | 36=6x+5x+3 | | 3x-20=x-15 |